Association between weight-adjusted-waist index and heart failure: Results from National Health and Nutrition Examination Survey 1999–2018 - Zhang, Daoliang; Shi, Wenrui; Ding, Zhaohui; Park, Jieun; Wu, Shaohui; Zhang, Jian (Frontiers in Cardiovascular Medicine, 2022)
Background: Weight-adjusted waist circumference index (WWI) is a novel index positively associated with excessive fat accumulation. The current study aims to evaluate the association between WWI and the prevalent heart failure (HF), and to assess the value of WWI to improve the detection of HF in the general population. Methods: 25509 subjects from National Health and Nutrition Examination Survey 1999-2018 were included into our study. WWI was calculated as WC (cm) divided by the square root of weight (kg). HF was identified according to the subjects’ reports. Results: The prevalence of reported HF was 2.96%. With adjustment of demographic, anthropometric, laboratory, and medical history data, one SD increment of WWI could cast an additional 19.5% risk for prevalent HF. After separating WWI into quartiles, the fourth quartile had a 1.670 times risk of prevalent HF compared to the first quartile. Furthermore, smooth curve fitting suggested that the association was linear in the entire range of WWI. Moreover, the association was robust to subgroups of age, sex, race, obesity, hypertension, and diabetes. Additionally, ROC analysis revealed a significant improvement for the detection of prevalent HF from WWI (0.890 vs. 0.894, P<0.001); And continuous net reclassification index (0.225, P<0.001) and integrated discrimination index (0.004, P<0.001) also supported the improvement from WWI. Conclusion: Our data demonstrated a significant, linear, and robust association between WWI, a simple surrogate for fat mass accumulation, and the risk for prevalent HF in a representative population. Moreover, our results also suggested the potential value of WWI to refine the detection of prevalent HF in the general population.